Five easy lessons : strategies for successful physics teaching - Knight, Randall Dewey, ....- (San Francisco (Calif.) : Addison-Wesley, 2004)
This widely admired standalone guide is packed with creative tips on how to enhance and expand your physics class instruction techniques. It's an invaluable companion for novice and veteran professors teaching any physics course.
Keywords: Natuurwetenschappen -- Didactiek; Physics -- Study and teaching; Physics